2008
DOI: 10.1177/0741932508324404
|View full text |Cite
|
Sign up to set email alerts
|

Career Ambitions

Abstract: Participants with and without specific learning disabilities (SLD) provided responses as to background and school features, postschool plans, dream career, and most likely job after completing school. Findings suggest that participant groups are similar across most background and school features, with apparent differences for grade level and repeating of a grade (participants with SLD older and more likely to have repeated a grade), and gender (those with SLD more likely to be male). Participants without SLD r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Perhaps the most important outcome of this study revealed the trajectory of occupational aspirations for people with high-incidence disabilities. We expected to find aspiration change patterns similar to those reported for adolescents without disabilities (Lee & Rojewski, 2009), albeit lower in prestige scores (Kortering, Braziel, & McClannon, 2010;Rojewski, 1996Rojewski, , 1999. Our analysis revealed this to be the case.…”
Section: Trajec T O R I E S a N D Change I N Occ U Pat I O N A L Aspisupporting
confidence: 72%
“…Perhaps the most important outcome of this study revealed the trajectory of occupational aspirations for people with high-incidence disabilities. We expected to find aspiration change patterns similar to those reported for adolescents without disabilities (Lee & Rojewski, 2009), albeit lower in prestige scores (Kortering, Braziel, & McClannon, 2010;Rojewski, 1996Rojewski, , 1999. Our analysis revealed this to be the case.…”
Section: Trajec T O R I E S a N D Change I N Occ U Pat I O N A L Aspisupporting
confidence: 72%
“…Adolescents with disabilities from middle or high socioeconomic status (SES) families had higher postsecondary education enrollments than those with disabilities from low SES families (Wagner et al, 2005). Kortering, Braziel, and McClannon (2010) reported that students with learning disabilities were more likely to have lower educational and occupational aspirations than those without disabilities. Factors influencing these lowered rates of enrollment and persistence of students with disabilities in college are not clear.…”
Section: Persistence In Postsecondary Educationmentioning
confidence: 99%
“…Later studies based on data from the early 2000s identified similar post–high school aspiration disparities. A 2002 student survey on post–high school plans revealed that students with learning disabilities were more likely to indicate they would move directly into working than attending a 4-year university, while the contrary was true for students without learning disabilities (Kortering et al, 2010). Furthermore, students with disabilities indicated that they intended to obtain jobs that required less education while their peers without disabilities indicated they would obtain jobs that required postsecondary education (Kortering et al, 2010).…”
Section: Disparities Between Youth With and Without Disabilitiesmentioning
confidence: 99%
“…In addition, previous studies noted limitations regarding disability label accuracy across time points (e.g., Rojewski, 1996) and using data to discuss post–high school aspirations with a sample of all high school graduates (Murray, Goldstein, Nourse, & Edgar, 2000), which could have biased results. Last, little is known about aspirations of students in education beyond students with learning disabilities, which has been a narrower focus of previous research (e.g., Kortering, Braziel, & McClannon, 2010). We address these limitations in the current study by utilizing more recent data from a large-scale sample of high school students with and without disabilities.…”
mentioning
confidence: 99%